Determination of Heavy Metals Concentration in Water and Soil at Various Locations in Lahore and their Harmful Impacts on Human and Plants life - Ayesha Noreen, Sajid Hussain, Umer Farooq, Tasaddaq Younas, Rahid Khan, Mohamed Gamal Elsehrawy (Pakistan Journal of Medical & Health Sciences, 2022)
Heavy metals poisoning of soil and water has resulted from industrial expansion in Lahore, Pakistan, creating a significant environmental hazard. As a result, monitoring the contamination of soil and water around industrial sites is critical. The fact that higher concentrations of heavy metals have a negative influence on both plants and human life and this cannot be ignored. Higher heavy metal concentrations have a direct impact on human health due to their presence in drinking water. Consumable plants and vegetables cultivated in these polluted areas may collect higher concentrations of heavy metals from soil and water via the phytoremediation process. Its worth mentioning that the accumulation of toxic metals in edible plants and vegetables also has a direct negative impact on human and animal health. The purpose of this study is to find the heavy metals concentration in the soil and ground water in the Lahore area. Five industrial zones were evaluated for water and soil throughout the research period of December 2021 to January 2022 (pre-monsoon). pH and heavy metals content measurements were performed on the collected soil and water samples. We discovered that the water had a higher pH and that the soil was heavily contaminated with significantly higher concentrations of toxic heavy metals. According to the research, there is a gangrenous influence of pollution caused by industrial waste and the surrounding environment on soil and water resources, which affects living creatures. Keywords: Environmental Pollution, Heavy Metal, Pollution, Water pollution, Soil pollution